Effects of a Liquefied Petroleum Gas Stove Intervention on Gestational Blood Pressure: Intention-to-Treat and Exposure-Response Findings From the HAPIN Trial. Issue 8 (16th June 2022) - Ye, Wenlu; Steenland, Kyle; Quinn, Ashlinn; Liao, Jiawen; Balakrishnan, Kalpana; Rosa, Ghislaine; Ndagijimana, Florien; Ntivuguruzwa, Jean de Dieu; Thompson, Lisa M.; McCracken, John P.; Díaz-Artiga, Anaité; Rosenthal, Joshua P.; et al.
Abstract : Background: Approximately 3 to 4 billion people worldwide are exposed to household air pollution, which has been associated with increased blood pressure (BP) in pregnant women in some studies. Methods: We recruited 3195 pregnant women in Guatemala, India, Peru, and Rwanda and randomly assigned them to intervention or control groups. The intervention group received a gas stove and fuel during pregnancy, while the controls continued cooking with solid fuels. We measured BP and personal exposure to PM2.5, black carbon and carbon monoxide 3× during gestation. We conducted an intention-to-treat and exposure-response analysis to determine if household air pollution exposure was associated with increased gestational BP. Results: Median 24-hour PM2.5 dropped from 84 to 24 μg/m 3 after the intervention; black carbon and carbon monoxide decreased similarly. Intention-to-treat analyses showed an increase in systolic BP and diastolic BP in both arms during gestation, as expected, but the increase was greater in intervention group for both systolic BP (0.69 mm Hg [0.03–1.35]; P =0.04) and diastolic BP (0.62 mm Hg [0.05–1.19]; P =0.03). The exposure-response analyses suggested that higher exposures to household air pollution were associated with moderately higher systolic BP and diastolic BP; however, none of these associations reached conventional statistical significance. Conclusions: In intention-to-treat, we found higher gestational BP in the intervention group compared with controls, contrary to expected. In exposure-response analyses, we found a slight increase in BP with higher exposure, but it was not statistically significant. Overall, an intervention with gas stoves did not markedly affect gestational BP.